2017
DOI: 10.1186/s13395-017-0123-0
|View full text |Cite
|
Sign up to set email alerts
|

Absence of physiological Ca2+ transients is an initial trigger for mitochondrial dysfunction in skeletal muscle following denervation

Abstract: BackgroundMotor neurons control muscle contraction by initiating action potentials in muscle. Denervation of muscle from motor neurons leads to muscle atrophy, which is linked to mitochondrial dysfunction. It is known that denervation promotes mitochondrial reactive oxygen species (ROS) production in muscle, whereas the initial cause of mitochondrial ROS production in denervated muscle remains elusive. Since denervation isolates muscle from motor neurons and deprives it from any electric stimulation, no action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 71 publications
0
62
0
Order By: Relevance
“…Cepia3 mt (Kd 11 μM) exhibited significant preferential mitochondria localization (evaluated through its co-localization with mtDsRed). It was previously reported that in muscle fibers the maximal mitochondrial Ca 2+ increase reached during a prolonged depolarization pulse exhibits a small delay compared to the cytoplasmic Ca 2+ transient (Karam et al, 2017 ). Nevertheless, the kinetics of Cepia3 mt compared to other mitochondrial Ca 2+ sensors appears to be even slower (Rudolf et al, 2004 ; Karam et al, 2017 ); this might be explained by Cepia3 mt characteristics, other than its Kd (Suzuki et al, 2014 ).…”
Section: Discussionmentioning
confidence: 94%
“…Cepia3 mt (Kd 11 μM) exhibited significant preferential mitochondria localization (evaluated through its co-localization with mtDsRed). It was previously reported that in muscle fibers the maximal mitochondrial Ca 2+ increase reached during a prolonged depolarization pulse exhibits a small delay compared to the cytoplasmic Ca 2+ transient (Karam et al, 2017 ). Nevertheless, the kinetics of Cepia3 mt compared to other mitochondrial Ca 2+ sensors appears to be even slower (Rudolf et al, 2004 ; Karam et al, 2017 ); this might be explained by Cepia3 mt characteristics, other than its Kd (Suzuki et al, 2014 ).…”
Section: Discussionmentioning
confidence: 94%
“…Denervation is reported to cause muscle oxidative stress, evidenced by high level of reactive oxygen species (ROS) (Karam et al. ). ROS in turns upregulates PGC1 α expression via AMPK (Irrcher et al.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK-PGC1a pathway may selectively serve as a compensatory mechanism in soleus, in contrast to EDL that primarily uses AKT as compensatory mechanism during atrophy. Denervation is reported to cause muscle oxidative stress, evidenced by high level of reactive oxygen species (ROS) (Karam et al 2017). ROS in turns upregulates PGC1a expression via AMPK (Irrcher et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In support, skeletal muscle activity and inactivity decreases and increases mitochondrial ROS, respectively [21] , [22] , [23] , [24] . Further, surgically abolishing skeletal muscle activity increases mitochondrial ROS ex vivo [25] , [26] , [27] , [28] . We propose that: mitochondrial ROS are endogenous synaptic activity sentinels.…”
Section: Introductionmentioning
confidence: 99%